Different tools for estimating cardiovascular risk in Brazilian postmenopausal women - Nahás, Eliana Aguiar Petri [UNESP]; Andrade, Aline M. [UNESP]; Jorge, Mayra C. [UNESP]; Orsatti, Claudio L. [UNESP]; Dias, Flavia B. [UNESP]; Nahas-Neto, Jorge [UNESP] (Taylor & Francis, 2013)
Objective: To compare estimation of cardiovascular risk using the Framinghan Risk Score (FRS) and the presence of the metabolic syndrome (MetS) in postmenopausal women to prevent primary cardiovascular disease (CVD). Methods: This cross-sectional study included 497 Brazilian women (aged 45 years and amenorrhea >12months). Cardiovascular risk was calculated using the FRS that includes age, total cholesterol, HDL, systolic blood pressure and smoking status. Women showing three or more of the following criteria were diagnosed with MetS: waist circumference (WC) >88cm, blood pressure 130/85mmHg, triglycerides 150mg/dl, HDL<50mg/dl and glucose 100mg/dl. For statistical analysis, the Chi-square, Fisher's exact, and logistic regression (odds ratio-OR) were used. Results: The mean age was 55.3±7.0 years and time since menopause 7.2±5.9 years. Based on FRS, 72.4% of women were classified as low-risk, 16.5% moderate risk and 11.1% a high-risk. MetS was identified in 40% of the women, and 46.2% were considered of moderate risk for CVD, while 84.9% of those without MetS were classified as low-risk (p<0.001). The risk for CVD increased significantly with age at menopause (OR1.10; 95% CI, 1.04-1.17), time since menopause (OR1.13; 95% CI, 1.08-1.18), elevated triglycerides (OR1.03; 95% CI, 1.0-1.10) and presence of MetS (OR1.72; 95% CI 1.48-1.84). Conclusions: By using only FRS to estimate cardiovascular risk, a substantial number of postmenopausal women showing evidence of MetS were not identified, even though women with MetS are at higher risk of CVD. © 2013 Informa UK Ltd.
Keywords: Cardiovascular disease; Framinghan risk score; Menopause; Metabolic syndrome; cholesterol; glucose; high density lipoprotein; low density lipoprotein; triacylglycerol; adult; amenorrhea; cardiovascular disease; cardiovascular risk; cholesterol blood level; comparative study; cross-sectional study; female; Framingham risk score; glucose blood level; high risk population; human; immobilization; lipoprotein blood level; low risk population; major clinical study; menopause; metabolic syndrome X; physical activity; postmenopause; priority journal; smoking; systolic blood pressure; triacylglycerol blood level; waist circumference